Cervical spine clearance in the adult obtunded blunt trauma patient: A systematic review. (April 2019) - Veiga, Joana Raquel Santos; Mitchell, Kay
Abstract: Background: A missed cervical spinal injury could have devastating consequences. Patients with a suspected cervical spinal injury are kept in rigid collars for cervical immobilisation. Prolonged collar use has important clinical implications. A well-defined guideline related to the removal of cervical collars from adult obtunded blunt trauma patients has not been developed. Aim: We sought to determine if Magnetic Resonance Imaging offered a definitive benefit over Computer Tomography with respect to patient management. Method: We searched Ovid Online, EBSCO, NICE Evidence Journals, Medline, PubMED, BNI, CINAHL and Google Scholar as well as the grey literature. Data extraction and synthesis were performed on studies that compared the radiologic findings and clinical outcomes of Computer Tomography scan and Magnetic Resonance Imaging in this patient group. Results: There is evidence that supports the safe discontinuation of cervical collar use after a negative multidetector Computer Tomography scan result alone. Magnetic Resonance Imaging may detect a significant number of ligamentous injuries, but such injuries are rarely of clinical significance because they rarely alter clinical management. Its use should be limited to specific circumstances. Conclusion: It is important for institutions to re-examine the latest evidence regarding cervical spinal clearance in order to update their guidelines.